El comportamiento electoral en la megalópolis - Graizbord, Boris (El Colegio de México A.C., 1993)
Electoral Geography provides and interesting approach to the study of human spatial behavior. In this paper I try to bring together some economic and political analytical models to make sense on the 1988 presidential election results in the Mexico City Metropolitan Area and surrounding "megapolitan" region. From a "soft", empirical analysis it becomes clear that the votes in favor of the different parties in the political spectrum reflect the spatial structure and areal differentiation of the region.